Differentially expressed circulating microRNAs in the development of acute diabetic Charcot foot. (October 2018) - Pasquier, Jennifer; Ramachandran, Vimal; Abu-Qaoud, Moh'd Rasheed; Thomas, Binitha; Benurwar, Manasi J; Chidiac, Omar; Hoarau-Véchot, Jessica; Robay, Amal; Fakhro, Khalid; Menzies, Robert A; Jayyousi, Amin; Zirie, Mahmoud; et al.
Aim: Charcot foot (CF) is a rare complication of Type 2 diabetes (T2D).Materials & methods: We assessed circulating miRNAs in 17 patients with T2D and acute CF (G1), 17 patients with T2D (G2) and equivalent neuropathy and 17 patients with T2D without neuropathy (G3) using the high-throughput miRNA expression profiling.Results: 51 significantly deregulated miRNAs were identified in G1 versus G2, 37 in G1 versus G3 and 64 in G2 versus G3. Furthermore, we demonstrated that 16 miRNAs differentially expressed between G1 versus G2 could be involved in osteoclastic differentiation. Among them, eight are key factors involved in CF pathophysiology.Conclusion: Our data reveal that CF patients exhibit an altered expression profile of circulating miRNAs